Anticoagulation in neurointerventions: basic pharmacology and pathophysiology, current status, practical advice - Scharf, Johann; Dempfle, Carl-Erik (Clinical neuroradiology, 2012)
This article gives an overview of anticoagulative medication accompanying neurointerventional procedures. The basic pharmacology of prevalent medication is outlined and the thrombogenicity of standard procedures is described. A brief overview of the literature on risks and benefits of standard medications and their monitoring is provided. A customized regime of care is presented.